Perkawinan Beda Agama dalam Perspektif Hak Asasi Manusia di Indonesia - Made Widya Sekarbuana; Ida Ayu Putu Widiawati; I Wayan Arthanaya (Warmadewa Press, 2021)
Presence of law number 1 Year 1974 about marriage can not provide legal protection as a whole in every marriage phenomenon, particularly in marriage different religions in Indonesia. Marriage law legitimately based on religion, but on human rights as privileges asserted freedom and marriage customs, embraced religion as a fundamental right that cannot be intervened by anyone. Problems of research 1) How marriage settings different religions in Indonesia? 2) How different religious marriage is a logical consequence of human rights perspective? This research is normative method, legal research with the study of the library of primary and secondary legal materials. Based on the findings of the research: 1) the Act of marriage has not provided certainty for couples who make marriage difference religion, there’s still a void marriage norms about different religions and conflict norms regarding legitimately marriage. 2) Different religious marriage discriminatory, religion is fundamental right that has been reserved and disinterfacking, the phenomenon raises consequences for one party with bowed themselves follow the religion of her partner. The Government expected to conduct observations regarding the effectiveness of the rules marriage and harmonization in Indonesia was not going empty, blurred or conflict of norms.